2019
DOI: 10.1371/journal.pone.0220658
|View full text |Cite
|
Sign up to set email alerts
|

The effect of trust and proximity on vaccine propensity

Abstract: The main goal of this paper is to study the effects of (1) trust in government medical experts and (2) proximity to a recent disease outbreak on vaccine propensity. More specifically, we explore how these variables affect attitudes with regards to measles. Using original survey data, collected in January/February 2017, we obtain three main empirical findings. First , contrary to our expectations, an individual’s proximity to a recent measles outbreak has no independent effect on vaccinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 38 publications
2
30
0
Order By: Relevance
“…What is not well understood, however, is how change in perceived risk translates into change in vaccine hesitancy. In other words, we do not yet have a sufficiently rich understanding of "vaccine propensity," a concept introduced by Justwan and colleagues [12] that we further advance here.…”
Section: Introductionmentioning
confidence: 97%
“…What is not well understood, however, is how change in perceived risk translates into change in vaccine hesitancy. In other words, we do not yet have a sufficiently rich understanding of "vaccine propensity," a concept introduced by Justwan and colleagues [12] that we further advance here.…”
Section: Introductionmentioning
confidence: 97%
“…[59][60][61] They have also characterized important relationships between vaccine confidence and contextual factors, such as geographical proximity to vaccine-preventable outbreaks and political trends. 62,63 Findings have also reinforced early impressions that while social media and other Web 2.0 tools are promising to disseminate accurate information on vaccines, they have also become a tool that has been leveraged more effectively by anti-vaccinationists than public health. 64,65 A recent analysis of Facebook responses to a South African HPV vaccination campaign found that while the majority of reactions (97%) on the page were favorable towards the vaccine, 33% of the comments were categorized as vaccine hesitant, "suggesting that people with negative reactions though few in numbers, were more likely to be vocal deniers".…”
Section: Canada Health Infowaymentioning
confidence: 77%
“… 59 61 They have also characterized important relationships between vaccine confidence and contextual factors, such as geographical proximity to vaccine-preventable outbreaks and political trends. 62 , 63 Findings have also reinforced early impressions that while social media and other Web 2.0 tools are promising to disseminate accurate information on vaccines, they have also become a tool that has been leveraged more effectively by anti-vaccinationists than public health. 64 , 65 …”
Section: A Digital Immunization System Of the Futurementioning
confidence: 80%
“…In addition, pharmacy users seek out community pharmacy services due to their accessibility and convenience, and without a physical space to engage regularly with pharmacy users, trust building between pharmacists and users is compromised. 64 …”
Section: Discussionmentioning
confidence: 99%